Screening and comparison of antioxidant activity of solvent extracts of medicinal plants grown in Turkey - AYAZ SEYHAN, SERAP; BİLĞİÇ ALKAYA, DİLEK (My University, 2022)
the developing world, the tendency towards natural antioxidants has increased due to the harmful effects of synthetic antioxidant use on the health. Hence, the researches on the antioxidant components in root, leaf and fruit of plant material are increasing day by day. Flavonoids and other phenolic compounds of plant origin have been reported as scavenger ROS, thus they are viewed as promising therapeutic drugs for free radical pathologies. The antioxidant activity of plant origin is dependent on the type and polarity of the extracting solvent as well as on the test system and the substrate to be protected by the antioxidant. The present study was undertaken to perform the screening of antioxidant properties of 3 medicinal plants (Lycium barbarum L,Morus nigra L and Inula helenium L grown in Turkey, and we selected 70% methanol and water as extract solvents which permits comparison of the antioxidant properties among the polarity based solvent extracts of medicinal plants. We used different extraction techniques, such as magnetic and ultrasonic stirrer, and the total phenolic content of the Lycium barbarum L., Morus nigra L. and Inula helenium L. extracts was determined by modified Folin-Ciocalteu method. The reducing power and radical scavenging activity of the extracts were also evaluated
Keywords: Lycium barbarum L.; Morus nigra L.; Inula helenium L.; extraction; antioxidant activity